Sistem Klasifikasi Saus Cabai mengandung Formalin dengan Sensor TCS3200 dan Sensor Groove-HCHO menggunakan Metode K-Nearest Neighbor berbasis Arduino - Hamzah Attamimi; Dahnial Syauqy; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Chili sauce is a sauce made using the main ingredient chili, which is processed by adding spices and permitted food ingredients, or without the addition of other foods. However, in Indonesia, the term fake sauce is often used to define sauces that contain ingredients that are harmful to the health of the body, one of the dangerous ingredients used is formalin. In checking chili sauce containing formalin carried out by experts by mixing a sample of sauce into a test tube and mixing it with a special formalin reagent, the results of the examination also require a long time. Based on these needs, it is necessary to design a system that can facilitate the checking of chili sauce containing formalin, and does not take much time in the inspection process. In this study, the detection system for chili sauce containing formalin used color parameters and formaldehyde gas content in the sauce sample. Arduino Mega microcontroller is used as a data processor on the system. The system will classify the Non-formalin and Contain Formalin data with the K-Nearest Neighbor method. In this study, 20 test data were applied in 60 training data used to determine the level of classification accuracy from the use of the K-Nearest Neighbor method with a value of K=3 of 85%, K=5 of 85%, and K=7 of 80%. Meanwhile, the average computation time obtained from 10 tests is 1807.3ms.